Local tissue reaction after the application of topical hemostatic agents in a rat partial nephrectomy model - Chalupová, Marta; Suchý, Pavel; Pražanová, Gabriela; Bartošová, Ladislava; Sopuch, Tomáš; Havelka, Pavel (Journal of biomedical materials research. Part A, 2012)
Various hemostatics are used for renal surgical procedures. We investigated the hemostatic efficacy of cellulose derivatives on the model of partial nephrectomy in rats focusing on the local reaction of renal parenchyma. A total of 50 Wistar rats were divided into five groups of 10 animals each. Partial nephrectomy of the caudal pole without hilar vascular control was performed. Oxidized cellulose (OC), sodium salt of oxycellulose (OCN), carboxymethyl cellulose (CMC), dialdehyde cellulose (DAC), and gelatin-based hemostatic (C) were applied to the bleeding wounds. The time to hemostasis was monitored. Half of the animals were euthanized after 3 days, the second half 30 days from the experiment start date. The left kidney was excised and subjected to histopathological examination. The biochemical data was subjected to statistical analysis. The time to hemostasis in all groups was significantly less than in the C group (in OC p = 0.0057, OCN p = 0.0039, CMC and DAC p = 0.0001). In the C group, massive hemorrhages and necrosis did occur. In the OC and OCN groups, there were regenerative changes, a receding inflammatory reaction and hemorrhage. DAC caused an immune reaction and massive interstitial hemorrhages with biochemical signs of liver damage. Parenchyma in CMC revealed a reduction of necrosis and interstitial hemorrhages with regenerative processes. The most effective hemostatics were CMC and OC, achieving the best results both in the time to hemostasis, and for histopathological evaluation.
Keywords: potkani Wistar; celulosa; ledviny; Rats; hemostáza; hemostatika; Animals; Hemostatics; Kidney; krysa rodu Rattus; Nephrectomy; nefrektomie; Rats, Wistar; Hemostasis; zvířata; Cellulose